Think pair share learning model based on 3d media in developing students' critical thinking skills - Mutmainnah Mutmainnah; Mohammad Djamil M. Nur; Siti Rabiatul Adawiyah (JPBIO (Jurnal Pendidikan Biologi), 2026)
Critical thinking skills is one of the essential competencies that must be developed in science learning, especially in the 21st century, as it enables students to analyze, evaluate, and solve problems effectively. Therefore, this study aims to determine the effect of the Think-Pair-Share (TPS) learning model based on three-dimensional (3D) media on the critical thinking skill of seventh-grade students at SMP Negeri 10 Palu on the topic of marine ecosystems. This study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The sample consisted of two classes, namely the experimental and control classes, selected through purposive sampling. The research instrument was an essay test consisting of 10 questions developed based on indicators of critical thinking, including interpretation, analysis, inference, explanation, and self-regulation. Data were analyzed using the Shapiro–Wilk normality test, Levene homogeneity test, and independent sample t-test at a significance level of 0.05. The results showed that the data were normally distributed and homogeneous. The hypothesis testing result obtained a significance value of 0.000 (<0.05), indicating that there was a significant difference in students’ critical thinking skills between the experimental and control classes after the treatment. These findings suggest that the implementation of the Think-Pair-Share learning model based on 3D media has a significant positive effect on improving students’ critical thinking skills.